A Keynesian-Minskian perspective on the transformation of industrial into financial capitalism - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2022)
The capitalism John Maynard Keynes struggled to analyse was clearly an industrial capitalism in which the investor used physical capital only to end up with more money than he started with. It is particularly the post Keynesian school of 'monetary or fundamentalist Keynesianism' which elaborated Keynes's monetary theory of production into an alternative economic paradigm that replaces the exchange ontology with an ontology based on nominal obligations. As economic history reports a higher speed of financial than real asset accumulation over the past half a century - a process often dubbed "financialisation" -, doubts have been raised as to whether this transformation of industrial capitalism into financialised capitalism demands for a new macroeconomic approach.
Keywords: 330; John Maynard Keynes; Hyman P. Minsky; monetary production economy; industrialcapitalism; financial capitalism; Financial Instability Hypothesis